Part a.
In order to find f(4) we need to substitute the value x=4 into the given function, that is,
![f(4)=2(4)+3](https://img.qammunity.org/2023/formulas/mathematics/college/vh10ba04nm76vnseie1yej9schy8jfpz33.png)
which gives
![\begin{gathered} f(4)=8+3 \\ f(4)=11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fb2uv7xtb79r3cmwlx2krypkv4i1w4rv3y.png)
Then, the ordered pair (4,11) is included in the function f(x).
Part b.
Similarly to the previous case, we need to substitute x=-1 into the function, that is,
![f(-1)=2(-1)+3](https://img.qammunity.org/2023/formulas/mathematics/college/yudm5u9esdn21sbuls70e63p187xbfwy0o.png)
which gives
![\begin{gathered} f(-1)=-2+3 \\ f(-1)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d4tmz0v1n1fr08f81c95ivfwgsf7ou4jvs.png)
So the ordered pair (-1,1) is included in the function f(x).